Craving Facebook? Behavioral addiction to online social networking and its association with emotion regulation deficits. (December 2014) - Hormes, Julia M.; Kearns, Brianna; Timko, C. Alix
Abstract Aims To assess disordered online social networking use via modified diagnostic criteria for substance dependence, and to examine its association with difficulties with emotion regulation and substance use. Design Cross‐sectional survey study targeting undergraduate students. Associations between disordered online social networking use, internet addiction, deficits in emotion regulation and alcohol use problems were examined using univariate and multivariate analyses of covariance. Setting A large University in the Northeastern United States. Participants Undergraduate students (n = 253, 62.8% female, 60.9% white, age mean= 19.68, standard deviation = 2.85), largely representative of the target population. The response rate was 100%. Measurements Disordered online social networking use, determined via modified measures of alcohol abuse and dependence, including DSM‐IV‐TR diagnostic criteria for alcohol dependence, the Penn Alcohol Craving Scale and the Cut‐down, Annoyed, Guilt, Eye‐opener (CAGE) screen, along with the Young Internet Addiction Test, Alcohol Use Disorders Identification Test, Acceptance and Action Questionnaire‐II, White Bear Suppression Inventory and Difficulties in Emotion Regulation Scale. Findings Disordered online social networking use was present in 9.7% [n = 23; 95% confidence interval (5.9, 13.4)] of the sample surveyed, and significantly and positively associated with scores on the Young Internet Addiction Test (P < 0.001), greater difficulties with emotion regulation (P = 0.003) and problem drinking (P = 0.03). Conclusions The use of online social networking sites is potentially addictive. Modified measures of substance abuse and dependence are suitable in assessing disordered online social networking use. Disordered online social networking use seems to arise as part of a cluster of symptoms of poor emotion regulation skills and heightened susceptibility to both substance and non‐substance addiction.